A companion to media authorship - Gray, Jonathan (Jonathan Alan); Johnson, Derek, 1979- (Wiley Blackwell, 2013)
"A Companion to Media Authorship offers 28 groundbreaking chapters which investigate the practices, attributions, and meanings of authorship. Revitalizing the study within media and cultural studies, this diverse and global collection provides the definitive work on the subject. -Rethinks cultures of authorship and challenges the concept of auteurism across multiple media forms -Moves beyond notions of the individual to focus on how authorship is collaborative, contested, and networked, examining cultures of authorship and the practicalities of how it works -Draws on the cutting-edge research of scholars and practitioners whose work has produced significant new insights into the field -Examines a wide range of media, including television, social media, radio, videogames, transmedia, music, and comic books -Offers an impressive global focus, including pieces on Mexican music, amateur film production in Nairobi slums, tele-serial production in Kinshasa, Hong Kong film, and the marketing of Bollywood"--